The Electronic Systems And Taxpayer Compliance - P. Hardiningsih, R. M. Oktaviani, R. Wahono, C. Srimindarti (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
Tax administration reform is a step taken by the government to increase the taxpayer compliance. This study aimed to examine and analyze the effect of e-Billing and e-Filing systems on the Ã‚Â taxpayer compliance. In addition, it was also meant to test and analyze the influence of understanding the internet as a moderating relationship between the implementation of the e-Filing system on the taxpayer compliance.The sample of 105 respondents. The results of this study indicated that the application of e-Billing system did not affect the taxpayer compliance, while the application of e-Filing system has a positive and significant effect on the tax compliance. While understanding the internet is proven to strengthen the positive relationship between the application of e-Filing system to the taxpayer compliance.